Analisis Altman Z-Score Untuk Mendeteksi Financial Distress Pada Perusahaan Perkebunan Kelapa Sawit yang Terdaftar di Bursa Efek Indonesia - Nurlaila Fitriani; Wawan Andang Saputra (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2025)
The palm oil industry is a vital pillar of the Indonesian economy, yet companies in this sector often face financial distress risks. This study explores the financial condition of palm oil plantation firms listed on the Indonesia Stock Exchange using the Altman Z Score method. Four key financial ratios, WCTA, RETA, EBITTA, and BVETL, were applied in the analysis. The sample was determined through purposive sampling and included sixteen companies with sixty four financial observations covering the years two thousand twenty to two thousand twenty three. Data were collected from annual reports and processed using Microsoft Excel, producing scores that classified companies into safe, grey, or distress zones. The results reveal that most firms maintained stability. In two thousand twenty three, seventy five percent of firms were in the safe zone, thirteen percent in the grey zone, and thirteen percent in the distress zone. Eleven firms consistently remained safe, one stayed in the grey zone, one persistently distressed, while three shifted between categories. These findings demonstrate that the Altman Z Score is not only an analytical tool but also a practical guide for investors in evaluating risk and shaping accurate investment strategies